The adequate organizational, administrative and accounting structure in smes: burden and honor - Morrone, Carla (Piccola Impresa / Small Business, 2021)
Legislative Decree no. 14 of 12th January 2019, in additionto replacing the bankruptcy law and establishing thenew Code of Business Crisis and Insolvency, introducedand amended some articles of the Italian Civil Code on themanagement and control of business activities. Indeed, theregulatory provision, which requires the appointment of acontrol body or auditor for small and medium-sized enterprises,also affects the management of the performing companiesand, in particular, the establishment by these entitiesof an internal control system. The analysis carried out isintended to highlight the benefits that small and mediumsizedenterprises could obtain implementing a valid andadequate organizational, administrative and accountingstructure